1988
DOI: 10.1016/s0022-5347(17)42403-7
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Histology in Fetuses with the Prune Belly Syndrome and Posterior Urethral Valves

Abstract: Intra-abdominal cryptorchidism and infertility are universal features of the prune belly syndrome but they usually are not seen with posterior urethral valves. To understand further the differences between these patients we reviewed testicular histology in 5 fetuses from each of 3 groups: prune belly syndrome, posterior urethral valves and normals. Spermatogonia were noted in all but the numbers were significantly reduced in those with the prune belly syndrome and posterior urethral valves compared to normals:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Despite surgical treatment, impaired fertility (33% in unilateral cases and 66% in bilateral undescended testes) and a cancer risk 5–10 times greater than normal is observed over time [ 15 ]. In PBS, the germinative epithelium is significantly reduced so testis descent should be performed in the newborn period to enhance the chances of fertility [ 5 – 8 , 17 ]. There are reports about live births of male infants resulting from intracytoplasmic sperm injection (ICSI) using spermatozoa from patients with PBS [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite surgical treatment, impaired fertility (33% in unilateral cases and 66% in bilateral undescended testes) and a cancer risk 5–10 times greater than normal is observed over time [ 15 ]. In PBS, the germinative epithelium is significantly reduced so testis descent should be performed in the newborn period to enhance the chances of fertility [ 5 – 8 , 17 ]. There are reports about live births of male infants resulting from intracytoplasmic sperm injection (ICSI) using spermatozoa from patients with PBS [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the germinative epithelium is significantly reduced and that seminiferous tubule diameter increases with age in sufferers of prune belly syndrome [ 5 – 8 ]. Nevertheless, structural and quantitative analyses of seminiferous tubules, extracellular matrix, and interstitial cells during the human fetal period in PBS are scarce in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Orvis et al also found that the numbers of foetal germ cells were reduced in foetuses with PUV [18]. However, this may be a consequence of the state of cryptorchidism, or an unrelated anomaly rather than part of the causative mechanism of cryptorchidism [19].…”
Section: Hormonal Imbalance Due To Renal Impairmentmentioning
confidence: 97%
“…Orvis et al [67] studied the testes from fetal specimens and noted reduced spermatogonia and Leydig cell hyperplasia. Conversely Nunn and Stephens [66] described normal testicular histology for age in autopsy specimens from newborns and prepubertal children.…”
Section: Cryptorchidismmentioning
confidence: 99%